Weaponisation of trespass to land and its implications for land justice and enjoyment of property rights in neoliberal Uganda - Nakayi, Rose (Strathmore Law Journal, 2023)
Protection of the right toproperty is among the central concerns of Uganda’s Constitution and laws. The law on civil and criminal trespass aims at facilitating enjoyment of property by prescribing damages for civil trespass and penalty for criminal trespass. Despite this, criminal and civil trespass have been used as weapons by some actors in land conflicts to undermine property rights of weaker parties and escalate land conflicts. The relationship among property, land conflicts and trespass is a theme of empirical significance in Uganda. Yet, weaponisation of trespass and its repercussions on property rights and resolution of land conflicts in Uganda is not significantly studied. This paper fills this gap. It conceptualizes criminal and civil trespass as embedded in the law, and how they have been weaponised. Using qualitative methods (analysis of literature, court decisions, and web based material) the paper finds that criminal trespass has been weaponized to target weaker parties to land conflicts hence impacting on their property rights and delivery of land justice. Using the criminal justice system, they are charged with criminal trespass, incarcerated, and are unable to pursue civil remedies from courts of law, hence protracting the underlying civil/land dispute. Civil trespass has also been misused within Uganda’s escalating land dispute terrain; in pursuit of selfish objectives rather than of justice. Uganda’s neoliberal context is an enabler of all the above. Recalibration of the civil justice system for efficience and amendment to section 302 to offer clarity on the boundaries of its application are recommended.